Pembentukan Nama Marga Karakter Dalam Manga Haikyu!! - Fifi Susanthy; Mohammad Ali (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2024)
Abstract The aim of the research is to describe the surnames formation in the manga Haikyu!! which will be reviewed in terms of the meaning of each kanji that forms it. The research method used is a qualitative descriptive research method. The research object is the surnames of the 10 members of the Karasuno High School volleyball club who appear in the manga entitled